Effect of soyflour and whey protein concentrate on cookie color - Pérez, Santiago (2013)
The objective of this work was to investigate the effect of soyflour and wheyproteinconcentrate (WPC) addition on the extent of Maillard reaction and caramelization during cookie baking. Wheat flour from a rotary molded cookie formulation was partially replaced by full fat soyflour and wheyproteinconcentrate. A central composite design was used and second order models were employed to generate response surfaces for loss of available lysine and for color development. Diffuse reflectance measurement of cookies was used to obtain the k/s coefficients of the Kubelka?Munk equation where k is the absorption coefficient and s is the scattering coefficient at 450, 557 and 680 nm. Luminance, dominant wavelength and excitation purity were also calculated. The addition of WPC produced an important increase in available lysine loss, k/s values and excitation purity, and a decrease in luminance and dominant wavelength. These results indicate that the addition of WPC favors the development of cookiecolor probably because of its high lactose content. On the contrary, the increment of water content produces a delay of Maillard reaction and caramelization. Soyflour had no significant effect on loss of available lysine and its effect on color parameter was much less significant than that of WPC.